The "hot money" phenomenon in Brazil - Mylène Gaulard (Brazilian Journal of Political Economy, 2012)
Because of its high interest rates, Brazil attracts more and more speculative capital flows, called "hot money", under the form of foreign loans, direct or portfolio investments. Actually, the country is directly involved in a carry-trade strategy that tends to appreciate the real, what penalizes the Brazilian exportations of manufactured products. Moreover, capital inflows are extremely volatile, and their departure, causing a fall in loans granted to the Brazilian private banks, could provoke a dangerous burst of the speculative bubble they have contributed to form in the Brazilian real estate sector.